The Role of Salam TV as Islamic Based Television in Promoting Interfaith Harmony in North Sumatera - Andini Nur Bahri; Ahmad Zueni (An Nadwah, 2021)
This study aims to determine the role of Salam TV in promoting harmony among religious communities in North Sumatera. This research method is a qualitative method that aims to get an in-depth description of speech, writing and behavior observed from an individual, group, community or organization in a specific setting which is studied from a comprehensive perspective. Salam TV does not produce programs that specifically feature harmony or tolerance. Salam TV's strategy in establishing harmony among religious communities is maintaining the shows that do not contain expressions of hatred that can trigger conflicts between religious communities. Institutionally Salam TV opens itself to work together in social and cultural fields to non-Muslim institutions.